A Comparison of the Wound Healing Efficacy of Trolamine Emulsion, Manuka Gel, and Polymyxin-Bacitracin Ointment. (April 2020) - Lu, Scott; Lu, Andrew; Paslin, David
ABSTRACT: OBJECTIVE: To compare the efficacy of three topical agents commonly used in cutaneous wound healing. METHODS: Wound healing was studied in 29 participants, and each participant served as his or her own control. In each participant, three similarly sized and located seborrheic keratoses were removed by curettage. Resultant wounds were treated with either trolamine emulsion, manuka honey gel, or polymyxin-bacitracin ointment until the wounds were fully healed. RESULTS: Wounds treated with trolamine emulsion healed significantly faster than wounds treated with either manuka honey or polymyxin-bacitracin (15 vs 19 days; P < .001). CONCLUSIONS: Trolamine emulsion may be preferred in clinical practice to accelerate the healing time of clean, shallow wounds.